Endoscopic Submucosal Dissection for Early Gastric Cancer using the Clutch Cutter: a large single-center experience - Akahoshi, Kazuya; Motomura, Yasuaki; Kubokawa, Masaru; Gibo, Junya; Kinoshita, Nobukatsu; Osada, Shigeki; Tokumaru, Kayo; Hosokawa, Taizou; Tomoeda, Naru; Otsuka, Yoshihiro; Matsuo, Mie; Oya, Masafumi; Koga, Hidenobu; Nakamura, Kazuhiko (Endoscopy International Open, 2015)
Background and study aims: The Clutch Cutter (CC) was developed to reduce the risk of complications related to endoscopic submucosal dissection (ESD) using knives. The CC is able to grasp and coagulate and/or incise the targeted tissue using electrosurgical current, like a biopsy technique. The aim of this study was to evaluate the efficacy and safety of ESD using the CC (ESD-CC) for early gastric cancer (EGC). Patients and methods: From June 2007 to March 2014, 325 consecutive patients with a diagnosis of EGC were enrolled in this prospective study. They had all satisfied the Japanese gastric cancer treatment guidelines for ESD indication, namely confirmation by preliminary endoscopy, endoscopic ultrasound, and endoscopic biopsies. The CC was used for all steps of ESD (marking, circumferential marginal incision, submucosal dissection, and hemostatic treatment). The therapeutic efficacy and safety were assessed. Results: The en-bloc resection rate was 99.7 % (324/325) and the R0 resection rate was 95.3 % (310/325). The mean operating time was 97.2 minutes. Perforation during ESD-CC occurred in one case (0.3 %), which was managed with conservative medical treatment after endoscopic closure of the perforation. Post-ESD-CC bleeding occurred in 11 cases (3.4 %), which were successfully treated by endoscopic hemostatic treatment. The R0 resection rate was significantly low in tumors > 20 mm (88.9 %), and in the exclusion indication group (73.7 %). Significant differences were seen in the mean operating time, depending upon tumor size, histologic type, location, and indication criteria. Conclusions: ESD-CC is a technically efficient, safe, and easy method for resecting EGC.